Performance of Uruguayan and foreign basketball players after the change of rule of the national competition - Corbo Olivera, Sebastian; Mier Ascarraga, Florencia; Gonzalez Ramirez, Andres (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
In 2017 the Uruguayan Basketball League incorporated a third foreign to the teams that could have affected the national’s player’s growth. The aim of this study was to compare the national and foreign player’s performance from the rule change that suggested an increase of foreign players, in the playoffs of the LUB 2017/2018 y 2018/2019 through the use of advanced statistics. The sample was 964 records of the 108 participating male players in 68 playoffs matches. It selected the metrics of Win Score (WS), Game Score (GS), Player Impact Estimate (PIE), Effective Field Goal Percentage (EFG%) and True Shooting Percentage (TS%) metrics as study variables. The result showed significant differences in all variables related to player productivity on the part of foreign from one season to the next (p<0,05) and in the comparison with the nationals (p<0,01), while the nationals showed differences related to shot from year to year. The foreign stood out with their productivity and their weight in the team's victories with scoring and rebounding role, while national players kept shot performances. Also, the foreign and national performance are not isolated, but they are complementary.